1994
DOI: 10.1161/01.str.25.1.160
|View full text |Cite
|
Sign up to set email alerts
|

Time course of variations in rabbit cerebrospinal fluid levels of calcitonin gene-related peptide- and substance P-like immunoreactivity in experimental subarachnoid hemorrhage.

Abstract: Background and Purpose Cerebral vasospasm after subarachnoid hemorrhage may result partially from the imbalance between vasodilator and vasoconstrictor factors. The vasodilator peptides substance P and calcitonin gene-related peptide contained in the trigeminovascular system are involved in the vasomotor phenomenon occurring after subarachnoid hemorrhage. The delayed arterial narrowing may reflect the time course of the release of these peptides. Therefore, we followed the time course of the changes in cerebro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Investigations into the temporary dynamics of sSAH-induced CGRP secretion are scarce and limited to the short-term [ 84 ]. As our sSAH patients significantly improved in multiple physical and emotional hrQoL items within 6 months, it might be reasoned that CGRP concentrations decrease or even normalize over time.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into the temporary dynamics of sSAH-induced CGRP secretion are scarce and limited to the short-term [ 84 ]. As our sSAH patients significantly improved in multiple physical and emotional hrQoL items within 6 months, it might be reasoned that CGRP concentrations decrease or even normalize over time.…”
Section: Discussionmentioning
confidence: 99%
“…Others (Tran Dinh et al, 1994) showed that the basal level of endogenous CGRP in CSF was 0.77 nmol/L in rabbits. The CGRP concentration peaked at 14 nmol/L within 30 min, and at 8 nmol/L within 24 h, after SAH.…”
Section: Calcitonin Gene-related Peptide and Sahmentioning
confidence: 99%